Efficacy and Safety of Adalimumab Biosimilars: Current Critical Clinical Data in Rheumatoid Arthritis - Lu, XiaoQin; Hu, Rui; Peng, Lin; Liu, MengSi; Sun, Zhen (Frontiers in Immunology, 2021)
Adalimumab, as a TNF inhibitor biologic for the treatment of rheumatoid arthritis, is one of the top-selling drugs worldwide. As its various patents gradually expired, experiments on its biosimilars are constantly being implemented. In this review, we summarized clinical trials of seven biosimilars currently approved by the FDA and/or EMA for the treatment of rheumatoid arthritis, namely: ABP 501 (Amjevita/Amgevita/Solymbic), BI 695501 (Cyltezo), SB5 (Imraldi/Hadlima), GP2017 (Hyrimoz/Hefiya/Halimatoz), MSB11022 (Idacio), FKB327 (Hulio), and PF-06410293 (Abrilada). As a result, these biosimilars showed similar efficacy, safety and immunogenicity to adalimumab. All biosimilars’ switching trials indicated that switching from adalimumab to biosimilar does not have a significant impact on efficacy, safety and immunogenicity.